Development and Validation of a Health-Related Quality-of-Life Measure in Older Children and Adolescents with Early-Onset Scoliosis: Early-Onset Scoliosis Self-Report Questionnaire (EOSQ-SELF). (3rd August 2022) - Matsumoto, Hiroko; Boby, Afrain Z.; Sinha, Rishi; Campbell, Megan L.; Hung, Chun Wai; Gbolo, Fay C.; Marciano, Gerard F.; Levine, Sonya; Fano, Adam N.; Simhon, Matthew E.; Quan, Theodore; Bainton, Nicole M.; et al.
Abstract : Background: The 24-question Early-Onset Scoliosis Questionnaire (EOSQ-24) is a proxy measure assessing health-related quality of life (HRQoL) among patients with early-onset scoliosis (EOS). There exists an increasing need to assess HRQoL through a child's own perspective, particularly for older children and adolescents with EOS. The purpose of this study was to develop and validate a self-reported questionnaire, the Early-Onset Scoliosis Self-Report Questionnaire (EOSQ-SELF), to assess HRQoL in older children and adolescents with EOS. Methods: A literature review, an expert focus group, and patient interviews were used to generate a preliminary survey of appropriate domains and question items. This survey was provided to English-speaking patients with EOS who were 8 to 18 years of age and capable of answering survey questions. Content validity was assessed for clarity and relevance of questions. Confirmatory factors analysis was performed to reduce the number of items and determine domains that fit items. Reliability was evaluated by measuring the internal consistency of items and test-retest reliability. Construct validity was evaluated by convergent, discriminant, and known-group validity. Results: The literature review, expert focus group, and patient interviews identified 59 questions in 14 domains. Psychometric analysis reduced these to 30 questions across 12 domains: General Health, Pain/Discomfort, Pulmonary Function, Transfer, Physical Function/Daily Living, Participation, Fatigue/Energy Level, Sleep, Appearance, Relationships, Emotion, and Satisfaction. The final questionnaire was found to have good content and construct validity and adequate reliability. Conclusions: The EOSQ-SELF is a valid and reliable instrument for measuring self-reported HRQoL among older children and adolescents with EOS (ages 8 to 18 years). This will serve as an important research outcome measure and enhance clinical care by providing a better understanding of HRQoL for these patients. Level of Evidence: Diagnostic Level II . See Instructions for Authors for a complete description of levels of evidence.